IMPLICATIONS OF DIFFERENTIATED INSTRUCTION STRATEGIES ON STUDENTS’ LEARNING OUTCOMES IN CIVIC EDUCATION - Adila Siti Maryam; Pat Kurniati; Prima Melati; Asep Anggi Dikarsa (Institut Pendidikan Indonesia, 2025)
This study analyzes the implications of differentiated learning strategies on students’ learning outcomes in Civics Education (PPKn) for grade X at SMAN 2 Garut. Differentiated learning is understood as an approach that adjusts content, process, and product of learning to students’ readiness, interests, and learning profiles, so that each learner receives appropriate support and challenge. The research employed a quantitative approach with a quasi-experimental nonequivalent control group design. The experimental class received differentiated learning, while the control class experienced conventional instruction. Data on learning outcomes were collected through pre-test and post-test instruments that had been validated, and analyzed using normality, homogeneity, and independent samples t-tests, complemented with N-gain scores to measure improvement. The results showed that the post-test mean score of the experimental class was higher than that of the control class, and the significance value of 0.017 indicated a statistically significant difference between both groups. The N-gain of the experimental class was categorized as moderately effective, while that of the control class was categorized as less effective. These findings indicate that differentiated learning strategies contribute positively to improving students’ learning outcomes in PPKn. The study suggests that teachers need to strengthen the implementation of differentiated learning by systematically mapping students’ characteristics and designing varied tasks, groupings, and assessments that align with Kurikulum Merdeka. The results are expected to become a reference for schools and teachers in developing learning practices that are more adaptive, inclusive, and oriented toward student needs. Future research can explore differentiated learning in other school subjects. Keywords: Differentiated Learning, Learning Outcomes, Civics Education